2013
DOI: 10.2131/jts.38.655
|View full text |Cite
|
Sign up to set email alerts
|

Imidacloprid, a neonicotinoid insecticide, induces insulin resistance

Abstract: exposures, which includes insecticides, and development of type 2 diabetes. However, there is limited -betes. Thus, the purpose of the study was to determine effects of imidacloprid, a neonicotinoid insecticide, on glucose metabolism. Three different cell models were used; adipocytes (3T3-L1), hepatocytes 4-6 days followed by treatment with insulin for 15 min to determine responses. Insulin stimulated glucose uptake was reduced by imidacloprid in all three cell culture models. Treatment with imidacloprid reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 44 publications
3
29
0
Order By: Relevance
“…Links between exposures to organochlorine and organophosphorus insecticides and increased risk of the development of type 2 diabetes in both humans and animals have been reported previously (Amanvermez et al, 2010; Cox et al, 2007; Everett et al, 2010; J. Kim et al, 2013; Lee et al, 2006; Lee et al, 2007; Rignell-Hydbom et al, 2007; Ukropec et al, 2010).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Links between exposures to organochlorine and organophosphorus insecticides and increased risk of the development of type 2 diabetes in both humans and animals have been reported previously (Amanvermez et al, 2010; Cox et al, 2007; Everett et al, 2010; J. Kim et al, 2013; Lee et al, 2006; Lee et al, 2007; Rignell-Hydbom et al, 2007; Ukropec et al, 2010).…”
Section: Discussionmentioning
confidence: 55%
“…Permethrin was previously reported to promote adipogenesis and induce insulin resistance in cell culture models, similar to other types of membrane-depolarizing insecticides (Howell et al, 2011; J. Kim et al, 2013, 2014; Moreno-Aliaga et al, 2002; Park et al, 2013; Shen et al, 2017; Sun, Qi, et al, 2016).…”
Section: Introductionmentioning
confidence: 75%
“…There is emerging evidence that exposures to organochlorine and organophosphorous insecticides are linked to increased weight gain and altered glucose homeostasis . Recently, we reported that imidacloprid, a neonicotinoid insecticide, promoted adipogenesis in 3T3‐L1 adipocytes and impaired insulin stimulated glucose uptake in C2C12 myotubes , suggesting potential involvement of insecticides on these biochemical responses. Moreover, chronic exposures to pyrethroids have been linked to adverse effects, such as increased blood glucose levels in animals and humans and small but a significantly higher body mass index in male pesticide factory workers involved in the manufacturing of pyrethroid products .…”
Section: Introductionmentioning
confidence: 93%
“…In particular, Pournourmohammadi et al (Pournourmohammadi et al, 2005) reported that this was due to increased activities of glycogen phosphorylase and phosphofructokinase (PFK), which are the key enzymes regulating glycogenolysis and glycolysis, respectively. In addition, permethrin (a pyrethroid insecticide) and imidacloprid (a neonicotinoid insecticide) were previously shown to induce insulin resistance in C2C12 muscle cells via Akt signaling (Kim et al, 2013, 2014a). …”
Section: Mechanisms Of Insecticide-induced Change In Glucose and Lmentioning
confidence: 99%
“…Although limited, other types of insecticides, such as carbamates, pyrethroids, and neonicotinoids, are associated with development of obesity and/or type 2 diabetes as well (Montgomery et al, 2008; Narendra et al, 2008; Saldana et al, 2007; Sun et al, 2016b; Wang et al, 2011b). More recently, in vitro and in vivo studies reported that pyrethroids, a neonicotinoid, and a phenylpyrazole (fipronil), all were involved in potentiated adipogenesis and/or altered glucose responsiveness, as representative of obesity and type 2 diabetes, respectively (Kim et al, 2013, 2014a; Park et al, 2013; Shen et al, 2017; Sun et al, 2016a; Sun et al, 2016b). Moreover, reports of interaction between dietary fat and insecticides on these markers, further begs the question of the role of insecticides and health.…”
Section: Introductionmentioning
confidence: 99%